Modulation of Aspergillus awamori Thaumatin Secretion by Modification of bipA Gene Expression - Lombraña, Marta (American Society for Microbiology, 2004)
Two different strains, Aspergillus awamori TGDTh-4 and A. awamori TGP-3 overexpressing a synthetic gene encoding the plant sweet protein thaumatin, showed an unfolded protein response. To facilitate protein secretion, the chaperone BiPA gene was expressed in A. awamori under control of the strong constitutive promoter of the gpdA gene. A good correlation was observed between the level of the bipA transcript in different strains and the amount of thaumatin secreted. Thaumatin secretion was increased 2- to 2.5-fold in transformants overexpressing the bipA gene compared with the parental strain. Secretion of the homologous proteins α-amylase and glucoamylase was not affected by the bipA gene overexpression. The requirement for BiPA for secretion of thaumatin was confirmed by attenuation of the endogenous bipA gene expression with an antisense RNA cassette. The decrease in bipA expression reduced the amount of secreted thaumatin up to 80% without affecting the secretion of the homologous α-amylase and glucoamylase proteins. The BiPA protein is, therefore, very important for secretion of some heterologous proteins, such as thaumatin in A. awamori.